Meningkatkan Kinerja Karyawan Pada Bisnis Vendor Katering: Dampak Hubungan Kerja dan Motivasi Kerja - Alvedia, Abril Amni; Herwanto, Dene; Fitriani, Risma (Universitas Kadiri, 2023)
The catering vendor business has a high opportunity to increase profits. However, the decreased working relationship and motivation had an impact on their performance during this time. Improving their performance requires the right factors of working relationships and motivation. This study is to determine the influence of these factors. Quantitative design with 24 respondents given a closed questionnaire to collect research data. Statistical testing as an appropriate tool to generate partial and simultaneous values of the case. The partial value of the employment relationship of 0.189 has no effect, motivation 3.025 has an effect on performance. A simultaneous value of 33.427 with a performance impact of 0.761. Employee collaboration and motivation have a positive impact on CV performance. Sabrina Usaha Mandiri with a value of 76.1%. The implementation of intensive labor relations and positive recognition of employees need to be improved. Flexibility in training also needs to be provided to improve performance and build a good company culture, so as to improve working relationships for the better and maintain increased work motivation for employee performance